Does academic writing coaching with genre pedagogy work with teachers? A case study of public school teachers in West Kalimantan, Indonesia - Aunurrahman, Aunurrahman; Netto-Shek, Jo-Ann; Irwan, Dedi; Putra, Muhammad Iqbal Ripo (Journal on English as a Foreign Language, 2024)
Recent studies in academic writing have used coaching to develop specific skills and affective variables. There are limited studies on coaching academic writing using genre pedagogy (GP) with adult learners, specifically Indonesian EFL teachers. This study investigated how academic writing coaching activities (AWCA) that implement GP could help develop the writing skills of public school teachers in Ketapang Regency, West Kalimantan, Indonesia. This qualitative case study involved fifty-seven participants who attended the coaching. Data obtained from participant observations and open-ended questionnaires were analyzed using inductive thematic analysis, and the participants